Momentum Transfer Effects in the Transport of Adsorbate at a Nano-Patterned Surface - David Nicholson; Suresh K. Bhatia (Adsorption Science & Technology)
Adsorbate molecules scattered in the repulsive field of a surface feature in the form of a semi-cylindrical stripe may be considered as a simple model for a nano-patterned surface. The extent of scattering was conveniently expressed as the tangential momentum accommodation coefficient. An analytical result was obtained using a simple local specular reflection hypothesis in contrast to the more complicated situation of an array of atoms discussed elsewhere, in which screening and secondary reflection may occur (Nicholson and Bhatia 2005). It was also demonstrated that a simple 2D representation leads to the same result for the tangential momentum accommodation coefficient.